IMPLEMENTATION OF IMAGE PROCESSING ALGORITHMS AND GLVQ TO TRACK AN OBJECT USING AR.DRONE CAMERA - Muhammad Nanda Kurniawan; Didit Widiyanto (Jurnal Ilmu Komputer dan Informasi, 2014)
Abstract In this research, Parrot AR.Drone as an Unmanned Aerial Vehicle (UAV) was used to track an object from above. Development of this system utilized some functions from OpenCV library and Robot Operating System (ROS). Techniques that were implemented in the system are image processing al-gorithm (Centroid-Contour Distance (CCD)), feature extraction algorithm (Principal Component Analysis (PCA)) and an artificial neural network algorithm (Generalized Learning Vector Quantization (GLVQ)). The final result of this research is a program for AR.Drone to track a moving object on the floor in fast response time that is under 1 second.